2022
DOI: 10.1136/bmjopen-2022-061297
|View full text |Cite
|
Sign up to set email alerts
|

How do high ambient temperatures affect infant feeding practices? A prospective cohort study of postpartum women in Bobo-Dioulasso, Burkina Faso

Abstract: ObjectiveTo examine the effects of high ambient temperature on infant feeding practices and childcare.DesignSecondary analysis of quantitative data from a prospective cohort study.SettingCommunity-based interviews in the commune of Bobo-Dioulasso, Burkina Faso. Exclusive breastfeeding is not widely practised in Burkina Faso.Participants866 women (1:1 urban:rural) were interviewed over 12 months. Participants were interviewed at three time points: cohort entry (when between 20 weeks’ gestation and 22 weeks’ pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Some of the physical consequences may seem relatively harmless in a country where maternal and neonatal mortality are high. But lack of hydration can affect health, as well as the duration of labour36–38 and breast feeding is very important for child survival 14. Also, dehydration is harmful and may cause kidney damage if its excessive 39.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the physical consequences may seem relatively harmless in a country where maternal and neonatal mortality are high. But lack of hydration can affect health, as well as the duration of labour36–38 and breast feeding is very important for child survival 14. Also, dehydration is harmful and may cause kidney damage if its excessive 39.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women and newborns are increasingly considered vulnerable populations in the context of climate change 13. Heat exposures in the first trimester are associated with an increased risk of maternal hypertension 14 15. Epidemiological studies have documented the impact of heat on certain perinatal complications and on rates of premature birth, low birth weight and stillbirth 9.…”
Section: Introductionmentioning
confidence: 99%
“…This is because they spend most of their time farming, were unlikely to attend antenatal clinics, and are less likely to receive information on optimal breastfeeding behaviors (23). In a study of infant feeding practices in Burkina Faso, we found an effect of high temperature after adjusting for the effects of the season (a 23-minute reduction in daily breastfeeding duration per 10°C increase in temp) (24).…”
Section: Introductionmentioning
confidence: 86%
“…High temperatures are known to have effects on mental health and wellbeing. High temperatures are associated with increased anxiety (24), lack of sleep (26, 27) and irritability (28). Infant care is very important for newborns.…”
Section: Introductionmentioning
confidence: 99%
“…In the setting of chronic heat exposure, breastfed newborns can suffer from dehydration, both from free water loss and insufficient human milk production to replace that deficit (Lusambili & Nakstad, 2023). Additionally, there is some evidence that extreme heat also makes it more difficult to exclusively breastfeed, especially for newborns less than 3 months of age (Part et al, 2022). Thus, extreme temperatures may contribute to reduced breastfeeding frequency and duration.…”
Section: Multidimensional Climate Influences and Human Healthmentioning
confidence: 99%